Identification of an elusive SERPING1 deletion in a family with hereditary angioedema type I utilizing soft clipping - Wetherby, Keith; Chiao, Joseph; Faulkner, Emily; Guo, Yongjian; Hou, Shaobin; Yu, J. Joanna; Chen, Jinguo; Wan, Lili; Henry Li, H. (Frontiers in Allergy, 2025)
BackgroundHereditary angioedema (HAE) is an autosomal dominant genetic disorder caused by mutations in the C1 esterase inhibitor gene, SERPING1, leading to overproduction of bradykinin and debilitating swelling attacks. Variants in the SERPING1 gene are typically detected in a clinical setting by DNA sequencing or multiplex ligation-dependent probe amplification (MLPA), with over 893 total variants identified. Approximately 5% of patients with C1-esterase inhibitor deficiencies do not have detectable SERPING1 pathogenic variants. We further investigated a family with laboratory-confirmed HAE type I despite previous negative genetic test results for SERPING1 mutations.MethodsWe consented and collected whole blood samples from three family members with clinical diagnoses of HAE. The samples underwent genomic DNA extraction and evaluation for purity prior to sequencing. The DNA samples were processed through a semi-automated whole exome library prep pipeline and sequenced. SERPING1 MLPA was performed to assess exon-level copy number variation (CNV) for exons 1 through 8. Additionally, we incorporated a well-established bioinformatics technique called soft clipping into our variant analysis pipeline to detect structural variants.ResultsClinical variant analysis revealed two common benign variants of SERPING1 in the proband. NGS and MLPA did not detect any SERPING1 pathogenic variants or genomic rearrangements, but additional structural variant analysis identified a high rate of soft clipping in exon 6 of the SERPING1 gene. Sanger sequencing of exon 6 revealed a heterozygous 56-base-pair deletion [NC_000011.10: g.57606508-57606563del, NM_000062(SERPING1): c.990_1029 + 16del] spanning the 3’ exon-intron boundary in all three subjects.SummaryWithout additional techniques following NGS and MLPA, such as a soft clipping analysis method, many difficult-to-detect large insertions and deletions may go undetected. We propose that a systematic approach to undetected HAE-causing mutation analysis, incorporating soft clipping as part of an overall strategy, would be more effective in identifying a small percentage of causal variants in approximately 5% of C1-esterase inhibitor HAE cases where no mutation is found by standard laboratory procedures, especially when there are high clinical suspicions of a familiar disorder.